الفروق في الذكاء الانفعالي بين الرياضيين من طلاب السنة الأولى في كلية التربية الرياضية في جامعة تشرين - ماضي, أنجيلا (Latakia University Journal -Medical Sciences Series, 2019)
This research aims to identify the level of emotional intelligence among students of the Faculty of Physical Education in addition to studying differences in this level according to sex and type of sport practice (individual or collective). The scale was distributed by first-year students at the Faculty of Physical Education. The sample consisted of (87) students (34 male and 53 female), of whom 63 were practicing collective sports and 24 were practicing individual ones. The Bar-on Scale of Emotional Intelligence is used to measure the emotional intelligence of people aged 7 to 18 years. The results of the study indicated that the level of emotional intelligence among the students was moderate, and also confirmed the existence of differences of statistical significance in the level of emotional intelligence attributed to the gender variable and for the benefit of females. In addition, there were no differences in the level of emotional intelligence in the research sample used for individual or group games. هدف هذا البحث الى التعرف على مستوى الذكاء الانفعالي لدى الطلاب الرياضيين في كلية التربية الرياضية بالإضافة إلى دراسة الفروق في مستواه تبعاً لمتغيري الجنس ونوع الرياضة الممارسة (فردية أو جماعية). وزع المقياس على طلاب السنة الأولى في كلية التربية الرياضية. تألفت عينة البحث من (87) طالباً، (34 ذكراً و53 أنثى)، منهم (63) ممارساً لرياضة جماعية و (24) ممارساً لرياضة فردية. استخدم في هذا البحث مقياس Bar-onللذكاء الانفعالي المصمم لقياس الذكاء الانفعالي للأشخاص من أعمار 7-18 سنة. أشارت نتائج الدراسة إلى أن مستوى الذكاء الانفعالي لدى الطلبة كان متوسطًا، كما أكدت وجود فروق ذات دلالة إحصائية في مستوى الذكاء الانفعالي تعزى لمتغير الجنس ولصالح الإناث. إضافة لذلك تبين عدم وجود فروق في مستوى الذكاء الانفعالي عند عينة البحث الممارسين لألعاب فردية أو جماعية.